Antioxidant and antimitotic activities of sulfated polysaccharide from marine brown algae Padina tetrastromatica - Jose, Geena Mariya; Radhakrishnan, Anitha; Muraleedhara Kurup, G (Journal of Phytology, 2015)
Antioxidants play a central role in the prevention of carcinogenesis. The most natural compounds exhibit their protective effects by eliciting antioxidant potential. Sulfated polysaccharide was isolated from the brown algae Padina tetrastromatica, then purified and evaluated for its composition and in vitro antioxidant and antimitotic activities. Both ethanolic sulfated polysaccharide (ESPS) and ethanolic sulfated polysaccharide-column purified (ESPS-CP) exhibited considerable amount of carbohydrates (11.2% and 17.6%), sulfate (11.4% and 7.4%), fucose (5.5% and 15.7%), uronic acid (4.7% and 11.8%), xylose (0.5% and 0.03%) and sulfated polysaccharide (2.4% and 12.7%) content. The FTIR analysis and phytochemical screening also confirmed the presence of sulfated polysaccharides. In the in vitro antioxidant activity determination using DPPH (1-1-diphenyl 2-picryl hydrazyl) radical scavenging activity, hydroxyl radical scavenging activity, superoxide anion scavenging activity, hydrogen peroxide scavenging activity, total antioxidant activity and reducing power, ESPS showed more activity than ESPS-CP. In the case of nitric oxide radical scavenging, ESPS-CP was found to be more effective. At a concentration of 2mg/ml, both samples were potent antioxidants with significant IC50 values. The antimitotic studies such as mitotic index in onion root tips and sprouting assay in green gram seeds also proved that both the extracts are able to prevent mitosis. The extrapolation of these results can find opportunities in therapeutic regiments of cancer.